Web-Based Souvenir Ordering Information System for Pasuruan: Sistem Informasi Pemesanan Oleh – Oleh khas Pasuruan Berbasis Web - Ansa, Mochamad Musaddat; Astutik, Ika Ratna Indra (Universitas Muhammadiyah Sidoarjo, 2022)
Dry Bakpia is a typical food from Pasuruan city made from green beans. One place that produces bakpia in a simple and conventional way is a new bakpia shop. In a survey conducted by the new bakpia shop, they still use the manual system, at this time the new bakpia shop is experiencing difficulties in selling production.The Covid-19 pandemic has an impact on all sectors, including business actors or MSMEs. For this reason, a final project or thesis entitled